2018
DOI: 10.1007/s12161-018-1332-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flavonoids and Phenolic Acids in Plant Materials Using SLE-SPE-UHPLC-MS/MS Method

Abstract: Today, great emphasis is placed on the search for and dissemination of native plant materials in various industries, with particular emphasis on food, cosmetics, dietary supplements, and as livestock feed and a source of biomass. Solid-liquid extraction (SLE), solid phase extraction (SPE), and ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) methods were developed for the simultaneous determination of 30 flavonoids and phenolic acids in plant materials (lucerne (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 23 publications
7
58
0
Order By: Relevance
“…In this work, the authors concluded that LLE is more effective for phenolic acids and flavonoids, whereas for anthocyanin extraction by SPE is better. Similarly, Bajckacz [31] compared solid-liquid extraction with the QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) method for the extraction of flavonoids and phenolic acids in plant material. QuEChERS is a novel extraction method created to avoid the use of large solvent volumes and to reduce the purification times [46].…”
Section: Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the authors concluded that LLE is more effective for phenolic acids and flavonoids, whereas for anthocyanin extraction by SPE is better. Similarly, Bajckacz [31] compared solid-liquid extraction with the QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) method for the extraction of flavonoids and phenolic acids in plant material. QuEChERS is a novel extraction method created to avoid the use of large solvent volumes and to reduce the purification times [46].…”
Section: Extractionmentioning
confidence: 99%
“…For example, some phenolic compounds are very photosensitive, as a result, rapid extraction methods are necessary to avoid the degradation of them [28]. Liquid-liquid extraction (LLE) and solid-liquid extraction (SLE) followed by a stage of concentration and purification are the most widely used methods to make a selective extraction of phenolic compounds from various matrices [2,3,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic, p-coumaric, ferulic, sinapic, 3-hydroxyphenylacetic, 3,4-dihydroxyphenylacetic (DOPAC), and homovanilic acids were also reported in phytochemical studies of S. virgaurea L [62]. In one study, whereas chlorogenic acid was detected and measured (by HPLC), ellagic and rosmarinic acids could not be detected [96].…”
Section: C6-c2 and C6-c3 Compoundsmentioning
confidence: 98%
“…antiadipogenic effects to kaempferol-3-O-rutinoside [104]. Several main compounds with a C6-C1 have apparently been reported up to date in S. virgaurea, two glycosides and two aglycones: virgaureoside A, a bis-desmosidic glycoside derived from benzoic acid (2-beta-D-glucopyranosyloxybenzoic acid-2'-beta-D-glucopyranosyloxybenzyl ester) [89], leiocarposide (2'-hydroxybenzyl-3-methoxybenzoate 2',4-diglucoside) [56], vanillic acid, gallic acid [9,90], benzoic acid, 3-hydroxybenzoic acid, 4-hydroxybenzoic acid, 3,4-dihydroxybenzoic (protocatechuic) acid, and 2,5-dihydroxibenzoic (gentisic) acid [61,62]. Such derivatives of the benzoic acid are often occurring in the family Asteraceae [91].…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation